Jejunogastric intussusception: A case report of unusual cause of upper gastrointestinal bleeding after gastrojejunostomy - Rajan, Swaminathan; Sivasankar Amarapathy,; Somasekar Durairajan, (Asian Journal of Medical Sciences, 2024)
Upper gastrointestinal bleeding is following gastrojejunostomy due to stromal ulceration, marginal ulcer bleeding from anastomotic site, remnant cancer. Gastrojejunostomy done for benign gastric outlet obstruction has many complications. Jejunogastric intussusceptions (JGI) is a rare complication of gastrojejunostomy surgery (<0.1% of cases), yet requires an urgent diagnosis. Mortality rates range from 10% to 50% based on delay in diagnosis and surgical intervention. Vomiting, abdominal pain, and hematemesis are the most common symptoms. We report a 53-year-old man admitted to the emergency department, complaining of epigastric pain and recurrent hematemesis for 3 days. Abdominopelvic computed tomography scan also showed a target sign in favor of jejunal intussusception. Midline emergency laparotomy was done and the gangrenous jejunum was resected with reconstruction Roux en Y loop was done. The patient was discharged without any further complications. In patients presented with hematemesis and abdominal pain and a history of gastrojejunostomy, JGI must consider a possible cause because early diagnosis and treatment are necessary to prevent further complications.